Strategies of corporate social responsibility in Latin America: a content analysis in the extractive industry (2017)
Latin American countries are rich in natural resources. In this regard, the extractive industry in the region is globally important. Consequently, the aim of this paper is to analyze the presence of the dimensions of Corporate Social Responsibility (CSR) in the strategies of the main extractive companies in Latin America, which include those listed in the ranking from “The greatest 500 companies of Latin America” from America Economía Magazine. In order to reach this assessment, a qualitative technique utilizing content analysis was carried out using the corporate web pages as a source of data. In addition, a matrix using 13 dimensions of CSR was developed to guide the research. 76 firms were identified from the extractive industry in Latin America, operating only in the mining and oil sectors. The main findings suggest that the majority of firms consider at least two dimensions of CSR, and that those such as the sustainable development and environment were those mentioned most. By country, Colombia shows the highest percentage of presence for these dimensions (86.2%). In addition, EXXONMOBIL and Carbones el Cerrejon (that operate in Colombia) include 100% of the dimensions. Future research will be important in order to analyze the extent to which the dimensions are fulfilled in practice, and to carry out comparative studies with other regions and industries.